Expression of phenylalanine ammonia lyase EgPAL2 from Elaeis guineensis Jacq. and its mutant EgPAL2ASG in Escherichia coli - Azhar, Aidil Hakim (2020)
Phenylalanine ammonia lyase (PAL) catalyses the conversion of L-phenylalanine to trans-cinnamic acid, the first step in the phenylproponoid pathway. The phenylproponoid pathway plays an important role in the production of diverse plant secondary metabolites important for defense and development. PAL is encoded by a small multiple gene family. The specific function of each PAL isoform is not easily predicted based on its expression pattern. In oil palm (Elaeis guineensis Jacq), PAL is encoded by five genes namely EgPAL1-EgPAL5. The EgPAL2 have no Ala-Ser-Gly (ASG) catalytic triad, highly conserved amino acids motif involved in the catalytic activity of PAL. The catalytic ability, the true substrate and the role of ASG triad in EgPAL2 were unknown. The objectives of this study were to determine the functionality of EgPAL2 at the protein level and to confirm that the ASG triad loss in EgPAL2 is the prime cause that converts EgPAL2 to a pseudogene. The ASG catalytic triad was inserted in EgPAL2 through a site-directed mutagenesis generating mutant EgPAL2 (EgPAL2ASG) to determine the role of ASG triad in EgPAL2 catalytic activity. The DNA coding sequence of EgPAL2 and its mutant EgPAL2 were subcloned into pET51b and expressed in E. coli BL21 (DE3). The protein expression was induced by isopropyl β-D-1-thiogalactopyranoside (IPTG). The recombinant protein was purified by using His-tag Ni-NTA purification column. The activities of EgPAL2 and EgPAL2ASG were determined by using L-phenylalanine, L-tyrosine and L-histidine as their substrates. Results showed that EgPAL2 did not have any activities on all tested substrates while EgPAL2ASG showed activities on L-phenylalanine and L-histidine but not L-tyrosine which suggested that the ASG triad was important for PAL catalytic activity. To date, there is no PAL activity on L-histidine was reported in plants which indicated that EgPAL2 was an ancient PAL which could have evolved from histidine ammonia lyase (HAL) from bacteria.